X-ray powder diffraction analysis of a silver(I) cyclamate complex - Putvinskis, R.; Santos, Carlos de Oliveira Paiva [UNESP]; Cavicchioli, M.; Massabni, Antonio Carlos [UNESP] (J C P D S-int Centre Diffraction Data, 2007)
X-ray powder diffraction data collected for the complex silver(I) cyclamate [Ag(C6H12NO3S)] are reported. This material was obtained from a stoichiometric mixture of sodium cyclamate and AgNO3. The analysis of the data using the Le Bail method showed that the complex has monoclinic symmetry (space group C2/c). The unit cell parameters are a=31.85852(16) angstrom, b=6.25257(6) angstrom c = 8.46165(7) angstrom, and beta=95.7651(5)degrees. (C) 2007 International Centre for Diffraction Data.
Keywords: silver(I); cyclamate; X-ray powder diffraction; Le Bail method